Language and executive function relationships in the real world: insights from deafness - Mario Figueroa; Nicola Botting; Gary Morgan (Language and Cognition)
Executive functions (EFs) in both regulatory and meta-cognitive contexts are important for a wide variety of children’s daily activities, including play and learning. Despite the growing literature supporting the relationship between EF and language, few studies have focused on these links during everyday behaviours. Data were collected on 208 children from 6 to 12 years old of whom 89 were deaf children (55% female; M = 8;8; SD = 1;9) and 119 were typically hearing children (56% female, M = 8;9; SD = 1;5). Parents completed two inventories: to assess EFs and language proficiency. Parents of deaf children reported greater difficulties with EFs in daily activities than those of hearing children. Correlation analysis between EFs and language showed significant levels only in the deaf group, especially in relation to meta-cognitive EFs. The results are discussed in terms of the role of early parent–child interaction and the relevance of EFs for everyday conversational situations.